Identification Of Acanthamoeba spp. In Used Contact Lens Solution - Chan, Michelle; Saputri, Dewi (Talenta Publisher, 2022)
Contact lenses are the most popular devices used by many people around the world for vision correction, aesthetics, and therapeutic purposes. Poor contact lens hygiene can cause various complications. One of the concerns regarding the use of contact lenses is the presence of Acanthamoeba spp. Acanthamoeba spp. is a free-living amoeba that can be found in many places including untreated fresh water, treated fresh water and unconventional water sources. One of the complications caused by Acanthamoeba spp. is Acanthamoeba keratitis which is an eye infection that is often caused by the use of contact lenses and contaminated contact lens solutions. Objective. The purpose of this study is to determine the description of Acanthamoeba spp. found in contact lens solution and contact lens care of Universitas Sumatera Utara students. Method. This study used univariate analysis. Data were obtained from the results of contact lens solution examination and questionnaire interviews. Result. Most of the samples (98%) did not have Acanthamoeba spp. Some respondents (60.8%) had fairly clean contact lens care behaviour and the rest (39.2%) had very clean contact lens care behaviour. Conclusion. One sample was found positive with Acanthamoeba spp. The positive sample had Acanthamoeba spp. cyst. Contact lens care was generally done well.